2011
DOI: 10.1016/j.ajpath.2010.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Deficiency Increases Liver Injury and Early Growth Response-1 (Egr-1) Expression in a Model of Chronic Xenobiotic-Induced Cholestasis

Abstract: Chronic cholestatic liver injury induced by cholestasis in rodents is associated with hepatic fibrin deposition, and we found evidence of fibrin deposition in livers of patients with cholestasis. Key components of the fibrinolytic pathway modulate cholestatic liver injury by regulating activation of hepatocyte growth factor. However, the exact role of hepatic fibrin deposition in chronic cholestasis is not known. We tested the hypothesis that fibrinogen (Fbg) deficiency worsens liver injury induced by cholesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 42 publications
6
27
0
Order By: Relevance
“…1A). Similar hepatic fibrin deposition has been reported previously in mice fed ANIT diet for 2 weeks (Luyendyk et al, 2011). It is noteworthy that we did not observe a statistically significant increase in hepatic fibrin deposits in TA-treated mice (data not shown).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…1A). Similar hepatic fibrin deposition has been reported previously in mice fed ANIT diet for 2 weeks (Luyendyk et al, 2011). It is noteworthy that we did not observe a statistically significant increase in hepatic fibrin deposits in TA-treated mice (data not shown).…”
Section: Resultssupporting
confidence: 73%
“…Hepatic fibrin deposition is evident in patients with chronic cholestatic liver disease (Luyendyk et al, 2011) and in rodent models of chronic cholestasis (Wang et al, 2007c;Luyendyk et al, 2011). Genetically imposed loss of fibrin(ogen) increases hepatic inflammation and injury in mice fed ANIT diet (Luyendyk et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, liver fibrosis is reduced in PAR-1 knockout mice and in mice treated with a PAR-1 antagonist [17,18]. Interestingly, recent studies showed that fibrin is deposited in the livers of patients with fibrosis indicating that even though coagulation factors may be depleted in patients with diminished liver function, sufficient liver function is present to activate the coagulation system locally in the liver, which may stimulate HSC proliferation in a PAR-1-dependent manner [19].…”
Section: Mediators That Stimulate Hsc Proliferationmentioning
confidence: 99%